La schiava fortunata ó vero La dori dramma musicale in three acts - Cesti, Antonio 1623-1669 (Naxos Rights (Europe) Ltd, 2020)
Pietro Antonio Cesti was one of the most outstanding champions of seventeenth-century Venetian opera, and La Dori was both his greatest success and a major influence on the genre in the expressiveness of its arias and duets. The story is set in Babylon on the shores of the Euphrates and is a convoluted and richly tragicomedy tale of lost lovers, disguises, and mistaken identities filled with larger-than-life and colorfully costumed characters
Interpreten: Francesca Ascioti (Dori). Rupert Enticknap (Oronte). Federico Sacchi (Artaxerse). Francesca Lombardi Mazzuli (Arsinoe). Emőke Baráth (Tolomeo). Bradley Smith (Arsete). Pietro Di Bianco (Erasto). Alberto Allegrezza (Dirce). Rocco Cavalluzzi (Golo). Konstantin Derri (Bagoa). Accademia Bizantina. Ottavio Dantone (Dirigent)
Aufnahme: Innsbruck, Tiroler Landestheater, Großes Haus, Innsbrucker Festwoche der Alten Musik, August 2019
Bildformat: 16:9
Keywords: Operas; Feature films; Film; Blu-Ray-Disc